ROUTE SIMULATION TRANSPORTS POLYGONAL SECTION CANAL WITH COMPLEX PROGRAM - G. A. Alibekov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The paper considers the problem of modeling the optimal route of the canal conveying polygonal cross-sectional shape, which extends into the recess without artificially mount. Designed application planning such canals, are examples of calculation and graphical dependencies.